HETEROTOPIC OSSIFICATION IN ACETABULAR FRACTURES: SYSTEMATIC REVIEW AND META-ANALYSIS OF PROPHYLAXIS - BUENO,THIAGO SANCHEZ PIRES (2021)
ABSTRACT Objective: Heterotopic ossification is defined as the formation of trabecular bone in soft tissues. It is a common complication after surgical treatment of acetabular fractures. However, its prophylaxis and treatment are still controversial. The objective of this research is to evaluate the effectiveness of actions to prevent the development of heterotopic ossification after surgical correction of acetabular fractures. Methods: A systematic review was carried out with research in the databases PubMed/MEDLINE, Embase, LILACS and Cochrane until August 4, 2020, without restrictions on language and year of publication. Only randomized clinical studies carried out in humans without restrictions based on the dosage of treatments, use and duration of prophylaxis were included in this review. Results: Two studies compared the use of radiotherapy and indomethacin and three compared the use of indomethacin with a placebo or non-indomethacin group. The meta-analysis calculations did not indicate statistical differences between radiotherapy versus indomethacin (RR 1.45, IC 95% 0.97 to 2.17, p = 0,55) and indomethacin versus placebo or not indomethacin (RR 0.85, IC 95% 0.68 to 1.06, p = 0,59). Conclusion: There is insufficient evidence to affirm that the use of radiotherapy or indomethacin are effective to prevent the formation of heterotopic ossification after surgery for fractures of the acetabulum. In addition, the number of complications was higher in the indomethacin group when compared to placebo or no intervention. Level of Evidence I, Systematic Review.